Uncovering the Impact of Workload and Burnout on Turnover Intention: The Critical Role of Resilience to Work - Handayani, Novi; Pujianto, Wahyu Eko (Lembaga Penelitian Universitas YARSI, 2024)
The purpose of this study was to determine how workload and burnout affect turnover intention moderated by job security in CV Yusima Teknik employees. The type of research used uses quantitative research. The population of CV Yusima Teknik employees was 37 people in this study. By using sampling techniques using saturated samples, so that the number of samples taken was 37 people. Data analysis in this study using Partial Least Square (PLS version 4.0). The results obtained are workload and burnout significantly positively affect the intention to move at CV Yusima Teknik, but work resilience can weaken this negative impact. And resilience has a significant negative effect on moving intention. The results of this study suggest the need for attention to workload management and burnout to reduce turnover intention in the company. Increasing resilience can also be an effective strategy in reducing the negative impact of workload and burnout on turnover intention.